Sexting in the public domain: competing discourses in online news article comments in the US and the UK involving teenage sexting. Issue 3 (3rd July 2018) - Jenkins, Elizabeth M.; Stamp, Glen H.
Abstract: The current study examined the phenomenon of teenage sexting through an analysis of 1030 comments from 15 online stories in the US and the UK. Four competing messages emerged: (1) Innocuity: Is sexting a harmless or harmful activity?; (2) Comparability: Were teenagers in the past the same or different than current teenagers?; (3) Criminality: Is teenage sexting a criminal offense or a legal activity?; and (4) Sexuality: Is teenage sexting sexual exploration or sexual exploitation? The online comments indicated an overall struggle between two different discursive constructions of sexting: A discourse of normal connection and a discourse of aberrant exposure. Implications of these findings are discussed.